PENGETAHUAN MEMPENGARUHI PERILAKU SEKSUAL PRANIKAH REMAJA - Tiwatu, Filia; Rakinaung, Natalia; Leong, Mentari (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2024)
Premarital sexual behavior among adolescents is an increasingly complex issue and needs serious attention. Along with the development of the era and changes in social values, adolescent sexual behavior is increasingly diverse. Factors that can influence adolescent sexual behavior are their level of knowledge about sexuality. Previous studies have shown that there is a relationship between knowledge about sexuality and adolescent sexual behavior, but the findings are still diverse. One key aspect in adolescent development is sexual knowledge and behavior. In the era of globalization and advances in information technology, adolescents have increasingly easy access to various information, including about sexuality. Adequate sexual knowledge is very important to help adolescents make responsible decisions regarding their reproductive and sexual health. Objective: to determine the effect of knowledge on adolescent premarital sexual behavior. Method: This study uses quantitative descriptive with an analytical observational approach. The population is all students in grades 10, 11, 12 of SMK Negeri 1 Tondano and the sample in this study is 251 students. Sampling using the purposive sampling method. Results: The results of the analysis using the Spearman rank test with p 0.001 so that knowledge has a significant relationship with premarital sexual behavior. Conclusion: knowledge influences premarital sexual behavior in adolescents.